2022
DOI: 10.1039/d2nj00512c
|View full text |Cite
|
Sign up to set email alerts
|

3D nanoporous NiCoP as a highly efficient electrocatalyst for the hydrogen evolution reaction in alkaline electrolyte

Abstract: Transition metal phosphides (TMPs) have demonstrated deep potential for accelerating electrocatalytic hydrogen evolution reaction (HER). Herein, we present the facile synthesis of nickel cobalt phosphide electrocatalyst with 3D nanoporous on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…After 12 h of continuous testing, the current density remained unchanged, and the results showed that the material also had good stability. The results of the synthesized electrocatalysts are compared with those of nickel phosphide reported in the literature, which show that the synthesized electrocatalyst has a better performance than nickel phosphide. We also provide a table comparing the HER activity of these catalysts to previously reported compounds, as shown in Table S5.…”
Section: Resultsmentioning
confidence: 95%
“…After 12 h of continuous testing, the current density remained unchanged, and the results showed that the material also had good stability. The results of the synthesized electrocatalysts are compared with those of nickel phosphide reported in the literature, which show that the synthesized electrocatalyst has a better performance than nickel phosphide. We also provide a table comparing the HER activity of these catalysts to previously reported compounds, as shown in Table S5.…”
Section: Resultsmentioning
confidence: 95%
“…ECSA on the other hand typically suggests more possible sites for catalysis. 53,54 Fig. 6e depicts C dl (in proportion to the ECSA) of a Co/NCNT-25 electrode as a function of scan rates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6d and Table S3 ECSA on the other hand typically suggests more possible sites for catalysis. 53,54 Besides high activity, another important criterion for highperformance electrocatalysts was to verify their long-term stability. [55][56][57] The Co/NCNT-25 catalyst was used to test the stability in 1 M KOH (Fig.…”
Section: Electrochemical Analysismentioning
confidence: 99%
“…2 Hydrogen production via electrocatalysis has gained more traction due to the properties associated with the electrocatalyst compared to those of other catalysts. 3–5 Overall water splitting (OWS) produces hydrogen via the hydrogen evolution reaction (HER) and oxygen via the oxygen evolution reaction (OER) at the cathode and anode, respectively as given in eqn (1) and (2).Cathodic reaction: 2H + + 2e − ↔ H 2 Anodic reaction: 2H 2 O ↔ O 2 + 4H + + 4e − …”
Section: Introductionmentioning
confidence: 99%